Meta Analysis: The Effect of Edmodo Assisted Physics Learning Media on Student Learning Outcomes - Naurah Nazifah; Nurul Azmi; Putri Nurhaliza; Desnita Desnita (Jurnal Penelitian Pendidikan IPA, 2021)
The industrial revolution 4.0 requires humans to have 21st century skills. In essence, education is expected to produce students who have the quality to live as individuals who are creative, innovative, intelligent, and globally competent. The purposes of this study are to: 1) Determine the effect of Edmodo media on student learning outcomes in the aspect of high school level class levels. 2) Determine the effect of Edmodo media on student learning outcomes on the material used. 3) Determine the effect of Edmodo media on student learning outcomes. The type of research used is meta-analysis. The articles analyzed in this study amounted to 15 articles published in 2014-2021. The average overall effect size of using Edmodo-assisted learning media on high school students' learning outcomes is 2.51 in the high category. The Edmodo-assisted physics learning media provides an effect size on the XI SMA level with an average of 2.91 in the high category, the Edmodo-assisted physics learning media provides an effect size on the XI SMA level with an average of 2.15 in the high category. The highest average value of the effect size of Edmodo-assisted learning media on global warming material with a value of 7.50 in the high category, while the lowest average value of the effect size of Edmodo-assisted learning media on optical instrument materials with a value of 0.87